The State's Obligation to Protect Children's Rights Under National and International Law - Miasiratni; Sri Agustini; Gokma Toni Parlindungan (Ekasakti Journal of Law and Justice, 2024)
The state's obligation to protect children's rights is not only based on national law but must also be in line with international commitments. The aim of the research is to analyze the extent to which the state fulfills its responsibilities in ensuring the protection of children's rights in accordance with international provisions, such as the Convention on the Rights of the Child (CRC), and national regulations, such as the Child Protection Law in Indonesia. The research method used is a normative juridical approach with analysis of legal documents, statutory regulations, and literature studies. The research results show that although the international legal framework has been adopted into national law, its implementation still faces various obstacles, including a lack of inter-institutional coordination, limited resources, and a lack of public understanding of children's rights. This journal recommends strengthening national regulations and increasing institutional capacity to ensure more optimal protection of children's rights.